Optimizing NKT cell ligands as vaccine adjuvants - Carreño, Leandro J (2014)
NKT cells are a subpopulation of T lymphocytes with phenotypic properties of both T and NK cells and a wide range of immune effector properties. In particular, one subset of these cells, known as invariant NKT cells (iNKT cells), has attracted substantial attention because of their ability to be specifically activated by glycolipid antigens presented by a cell surface protein called CD1d. The development of synthetic α-galactosylceramides as a family of powerful glycolipid agonists for iNKT cells has led to approaches for augmenting a wide variety of immune responses, including those involved in vaccination against infections and cancers. Here, we review basic, preclinical and clinical observations supporting approaches to improving immune responses through the use of iNKT cell-activating glycolipids. Results from preclinical animal studies and preliminary clinical studies in humans identify many promising applications for this approach in the development of vaccines and novel immunotherapies.